Elemental composition and bioaccessibility of three insufficiently studied Azorean macroalgae. (21st June 2020) - Afonso, Cláudia; Matos, Joana; Campos, Ana M.; Gomes, Romina; Delgado, Inês; Coelho, Inês; Castanheira, Isabel; Bandarra, Narcisa M.; Cardoso, Carlos
Summary: The elemental composition and bioaccessibility of the Azorean macroalgae Petalonia binghamiae, Osmundea pinnatifida and Halopteris scoparia were studied. H. scoparia had the highest Cr, Mn, Co and Ni contents. Iodine content was also the highest in H. scoparia, 1098 ± 54 mg kg dw −1 . Content reductions due to rehydration were in the 75%–90% range. Steaming led to similar reductions with exception of Cr, Mn, Co, Ni and Zn in O. pinnatifida . For P. binghamiae and O. pinnatifida, bioaccessibility percentages varied between elements. Variation due to rehydration and culinary treatment was narrower, particularly for P. binghamiae . Whereas I bioaccessibility was low in O. pinnatifida, 11%–14%, it reached 57%–69% in P. binghamiae . On the basis of bioaccessibility, to meet the I DRI, 2.7 g dried P. binghamiae, 16.9–23.8 g rehydrated P. binghamiae and 12.7 g steamed P. binghamiae everyday are required. For O. pinnatifida, 5.0 g, 19.0–33.3 g and 12.9 g of dried, rehydrated and steamed red seaweed, respectively, are needed. Abstract : Experimental design of the study conducted on the three Azorean macroalgae.